Utveckling av damm- och partikelhantering till autonom golvslip - Andersson, Wilma; Skogberg, Gideon (My University, 2023)
Polished concrete floors are becoming increasingly common in industrial premises and in homes. Grinding is a method to achieve a durable, sustainable and consistently smooth flooring solution. However, the process is time-consuming and demanding for the operator, who is exposed to noise, vibrations, and dust for extended periods of time. An autonomous concrete grinder would eliminate the operator from this demanding environment and moreover reduce the cost of the method. Husqvarna Construction manufactures machinery and tools for professional users and is a leader in diamond tools for grinding, cutting, and drilling. They intend to develop the field of floor grinding with the concept of an autonomous floor grinder, something which does not currently exist on the market. This thesis project aims at finding a solution for dust and particle management during the grinding of concrete floors using an autonomous floor grinder. The work was initiated with interviews and an investigation of existing products on the market to gain a good understanding of and insight into the problem. Subsequently, multiple ideas for solutions were generated, and then progressively inferior alternatives were eliminated until only one concept remained. It was evaluated using 3D models and a 3D-printed prototype, along with existing testing equipment and a prototype machine. The results of the concept testing were compared to a similar previous measurement conducted by the Dust and Slurry division at Husqvarna Construction, as an objective reference value is lacking. In this comparison, it was revealed that the levels of dust particles were higher for the developed concept compared to the product Husqvarna used during the test. However, the concept is considered a well-founded solution after further development.
Keywords: Concrete floor, autonomous floor grinder, Husqvarna, concrete grinder, floor grinder, autonomous